APPLICATION OF 3D DIGITAL SCANNING AND CAD/CAM SYSTEMS FOR ZIRCONIA INDIRECT RESTORATIONS - Mariela Tsanova; Neshka Manchorova-Veleva; Snejana Tsanova (Peytchinski Publishing, 2016)
Object: To study the CAD/CAM systems' possibilities for manufacturing Zirconia indirect restorations for restoring vital, vastly devastated teeth. Material and methods: Five patients with vital, heavily destroyed molars were included in the clinical study. The teeth were prepared according to requirements for Zirconia restorations. The impressions were taken with 3D intraoral scanner. The acquired data is transmitted electronically for designing the future restoration by the CAD software. After designing, the restoration is milled by the CAM module and sintered, according to a specially projected programme in accordance with the manufacturing demands. After clinical check-up, the restorations are glazed, air-blasted and cemented. Results: Setting up an individual protocol for working with CAD/CAM systems for restoring vital, severely devastated teeth with Zirconia indirect restorations. A research is made on 3D digital scanning, occlusal and proximal modeling, virtual articulation, analyzing the incline of the cavity walls, the thickness of the restoration and the possibilities for restoring the anatomy of the tooth according to patient's individual characteristics of the teeth's arch. Conclusion: The scanning and design process should be evaluated with the same quality control as when using traditional methods. The CAD software requires excellent preparation of the tooth cavity and digital scanning. This is the reason why these systems require a thorough understanding of CAD/CAM calibration and parameters of the product to be clinically acceptable. Once understood, CAD/CAM dentistry can create detailed and accurate restorations that function and perform with great success and longevity.